Safety Evaluation of Clearance of Radioactive Metal Waste After Decommissioning of NPP - 최영환; 고재훈; 이동규; 황영환; 이미현; 이지훈; 홍상범; Young-Hwan Choi; Jae-Hun Ko; Dong-Gyu Lee; Young-Hwan Hwang; Mi-Hyun Lee; et al. (Journal of nuclear fuel cycle and waste technology (Online), 2020)
영구정지후 해체가 계획된 고리 1호기 원자력발전소는 해체과정에서 다양한 종류의 방사성폐기물이 대량으로 발생될 것으 로 예상되고 있으며, 이 중 원자로 및 내부구조물은 방사능 수치가 높으므로 1차측에서 적절한 크기와 중량으로 해체된다. 고리 1호기 해체시 원자로 및 내부구조물에서 발생되는 방사성폐기물에 대하여 기존 폐기물의 자체처분 현황 및 법적 제한 사항 분석 등을 통해 적절하고 효율적인 처분방법을 마련하는 것은 중요한 사안일 것으로 판단된다. 원자로 및 내부구조물 에서 발생되는 폐기물은 중준위에서부터 자체처분까지 다양한 준위의 폐기물들이 발생되며, 이 중 자체처분 준위에 해당되 는 폐기물은 방사화 평가 결과, 원자로 상부 헤드와 상부 헤드 인슐레이션에서 발생되는 것으로 나타났다. 본 논문에서는 방사화 평가 결과를 바탕으로 자체처분 준위에 해당되는 폐기물을 자체처분 평가 코드인 RESRAD-RECYCLE 코드를 사용하여 자체처분 안전성 평가를 수행하였다. 대상 폐기물의 자체처분 시나리오를 선정하고 자체처분시 개인 및 집단별 최대선량을 계산하여 국내 원자력안전법에서 규정하는 자체처분 기준 제한치의 만족 여부를 판단하였다. 평가 결과, 전체적으로 상당히 낮은 결과값을 보이며 기준 제한치를 만족하는 결과를 나타내었으며, 핵종별 자체처분 허용농도를 도출하였다. The Kori-Unit 1 nuclear power plant, which is scheduled to be decommissioned after permanent shutdown, is expected to generate large amounts of various types of radioactive waste during the decommissioning process. Among these, nuclear reactors and internal structures have high levels of radioactivity and the dismantled structure must have the proper size and weight on the primary side. During decommissioning, it is important to prepare an appropriate and efficient disposal method through analysis of the disposal status and the legal restrictions on wastes generated from the reactors and internal structures. Nuclear reactors and internal structures generate radioactive wastes of various levels, such as medium, very low, and clearance. A radiation evaluation indicates that wastes in the clearance level are generated in the reactor head and upper head insulation. In this study, a clearance waste safety evaluation was conducted using the RESRAD-RECYCLE code, which is a safety evaluation code, based on the activation evaluation results for the clearance level wastes. The clearance scenario for the target radioactive waste was selected and the maximum individual and collective exposure doses at the time of clearance were calculated to determine whether the clearance criteria limit prescribed by the Nuclear Safety Act was satisfied. The evaluation results indicated that the doses were significantly low, and the clearance criteria were satisfied. Based on the safety assessment results, an appropriate metal recycle and disposal method were suggested for clearance, which are the subject of the deregulation of internal structures of nuclear power plant.